GATA‐1 Deficiency Rescues Trabecular but not Cortical Bone in OPG Deficient Mice. Issue 4 (April 2015) - Meijome, Tomas E.; Hooker, R. Adam; Cheng, Ying‐Hua; Walker, Whitney; Horowitz, Mark C.; Fuchs, Robyn K.; Kacena, Melissa A.
<x xml:space="preserve">Abstract</x> GATA‐1low/low mice have an increase in megakaryocytes (MKs) and trabecular bone. The latter is thought to result from MKs directly stimulating osteoblastic bone formation while simultaneously inhibiting osteoclastogenesis. Osteoprotegerin (OPG) is known to inhibit osteoclastogenesis and OPG−/− mice have reduced trabecular and cortical bone due to increased osteoclastogenesis. Interestingly, GATA‐1low/low mice have increased OPG levels. Here, we sought to determine whether GATA‐1 knockdown in OPG−/− mice could rescue the observed osteoporotic bone phenotype. GATA‐1low/low mice were bred with OPG−/− mice and bone phenotype assessed. GATA‐1low/low × OPG−/− mice have increased cortical bone porosity, similar to OPG−/− mice. Both OPG−/− and GATA‐1low/low × OPG−/− mice, were found to have increased osteoclasts localized to cortical bone, possibly producing the observed elevated porosity. Biomechanical assessment indicates that OPG−/− and GATA‐1low/low × OPG−/− femurs are weaker and less stiff than C57BL/6 or GATA‐1low/low femurs. Notably, GATA‐1low/low × OPG−/− mice had trabecular bone parameters that were not different from C57BL/6 values, suggesting that GATA‐1 deficiency can partially rescue the trabecular bone loss observed with OPG deficiency. The fact that GATA‐1 deficiency appears to be able to partially rescue the trabecular, but not the cortical bone phenotype suggests that MKs can locally enhance trabecular bone volume, but that MK secreted factors cannot access cortical bone sufficiently to inhibit osteoclastogenesis or that OPG itself is required to inhibit osteoclastogenesis in cortical bone. J. Cell. Physiol. 230: 783–790, 2015. © 2014 Wiley Periodicals, Inc.